The Effect of Maternity Support Garments on Alleviation of Pains and Discomforts during Pregnancy: A Systematic Review - Carolina Quintero Rodriguez; Olga Troynikov (Journal of Pregnancy)
Maternity support garments (MSGs) are widely available and commonly recommended and used for alleviation of lower back pain (LBP) and pelvic girdle pain (PGP) during pregnancy; however, most studies available use the garments as a conjunct intervention with other therapies, with scarce research demonstrating the effects of the garments as a sole intervention. This study aims to review the available literature on the effects of using MSGs as sole intervention for comfort improvement of women during pregnancy, as well as to discuss the attributes of the garments which may influence their performance. A systematic review was undertaken, which adheres to PRISMA guideline for systematic reviews. Multiple databases, such as ScienceDirect, CINAHL, EBSCO, Elsevier, SCOPUS, Wiley Online Library, ProQuest, ProQuest Health and Medical Complete, PubMed, and Cochrane Central Register of Controlled Trials, were electronically searched. Six studies met the inclusion criteria and covered three trial studies, two pilot studies and one observational study. Three outcome measurements were identified from the included studies: alleviation of pain, improvement of balance, and improvement of functionality and mobility. The study concluded that wearing MSGs during pregnancy could have beneficial effects in women such as LBP and PGP alleviation, improvement of functionality and mobility, and reduction of risk of fall during pregnancy; however, the mechanisms of the garments’ actions as well as the duration of the garments’ effectiveness are not elucidated through the studies. This study contributes to the understanding of the effects and effectiveness of the use of MSGs as a sole intervention for improvement of comfort during pregnancy as well as information about the different types of garments commercially available and the attributes that may influence the garment performance.